2019
DOI: 10.3390/toxins11100581
|View full text |Cite
|
Sign up to set email alerts
|

Alternative mRNA Splicing in Three Venom Families Underlying a Possible Production of Divergent Venom Proteins of the Habu Snake, Protobothrops flavoviridis

Abstract: Snake venoms are complex mixtures of toxic proteins encoded by various gene families that function synergistically to incapacitate prey. A huge repertoire of snake venom genes and proteins have been reported, and alternative splicing is suggested to be involved in the production of divergent gene transcripts. However, a genome-wide survey of the transcript repertoire and the extent of alternative splicing still remains to be determined. In this study, the comprehensive analysis of transcriptomes in the venom g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 39 publications
(54 reference statements)
1
21
0
Order By: Relevance
“…Similarly, amplification of a minor activity or escape from adaptive conflict between the cysteine-rich, disintegrin, or metalloproteinase domains could explain the evolution of P-II and P-I genes. It has recently been reported that alternative splicing of the SVMP genes in the habu snake (an Asian viper) can generate transcripts which encode different combinations of domains (48). Gene deletions that reduce the proteins from three to two domains (mdc to mad) or two to one domain (mad to mpo) would relieve potential conflict among isoforms and allow for optimization of minor activities.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, amplification of a minor activity or escape from adaptive conflict between the cysteine-rich, disintegrin, or metalloproteinase domains could explain the evolution of P-II and P-I genes. It has recently been reported that alternative splicing of the SVMP genes in the habu snake (an Asian viper) can generate transcripts which encode different combinations of domains (48). Gene deletions that reduce the proteins from three to two domains (mdc to mad) or two to one domain (mad to mpo) would relieve potential conflict among isoforms and allow for optimization of minor activities.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also highlighted the role of alternative-and trans-splicing in generating snake venom diversity (Figure 1). Genome-wide surveys of the transcriptional repertoire have led to the identification of alternative splicing in genes that encode SVMPs, snake venom serine proteases (SVSP) and vascular endothelial growth factors (VEGF), and trans-splicing in SVSP genes [42,46]. Rapid evolution under positive selection has been widely documented to facilitate adaptations in the natural world.…”
Section: The Processes That Underpin Venom Variationmentioning
confidence: 99%
“…All the smaller P. verdolagas' ORFs are hypothesized to be then smaller isoforms of the best score homolog proteins, as the Augustus prediction algorithm identi ed them as complete transcripts and the global identity was above 20% (51). The varying lengths of these ORFs, which represent 7 to 27% of the best score homolog proteins primary structure, could be indicators of splicing events within the venom gland of spiders, as it has been described before in other venomous species (53,54), and therefore could also imply similar biological function. On the other hand, ORFs with the smallest global identity show between 58 and 164% of the best homolog protein's length, implying enough variability within the primary structure as to assume probable different biological activities to those of their homologs (51).…”
Section: Potential New Toxins In the Venom Gland Of P Verdolagamentioning
confidence: 78%